Global aphasia without hemiparesis may be caused by blunt head trauma: An adolescent boy with transient aphasia - TÜRKDOĞAN, DİLŞAD; EKİNCİ, GAZANFER (ELSEVIER SCI LTD, 2017)
Global aphasia without hemiparesis is a rare condition often associated with embolic stroke. Posttraumatic causes have not been reported, in the literature, to our knowledge. We report a 15-year old boy with transient global aphasia without hemiparesis due to blunt head trauma. In our case, clinical findings occurred 1 week later following head trauma. Emergence of the symptoms after a period of the first mechanical head trauma, draws attention to the importance of secondary process in traumatic brain injury. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Global aphasia without hemiparesis; Posttraumatic aphasia; Traumatic brain injury; Aphasia